Strategic Managerial Accounting as a Means of Survival for Small and Medium Business - M. V. Shevelenko (Управленческие науки, 2017)
The strategic managerial accounting can become a means of survival for small and medium business (SMB) in the Russian economy during the period of crisis. The aim of the given article is work out the practical guidelines on implementing in the organizations of SMB the elements of strategic managerial accounting, the basic planning elements planning in particular. Within the framework of the conducted investigation the key development factors of SMB organizations have been detected. Six variants of implementing planning elements for SMB organizations have been elaborated on the basis of scenario approach with the account of Russian economic realities, as well as the actual and discounted magnitude of cash flows necessary for the conversion of each of them have been evaluated. In the result of investigation the conclusion has been made that implementing the elements of strategic managerial accounting, the current planning specifically, in the Russian organizations of SMB is necessary for their survival. It has been demonstrated that SMB organizations possess all the possibilities for implementing a short-term planning by themselves even under the sircumstances of crisis in the Russian economy.